A strategy for O-glycoproteomics of enveloped viruses--the O-glycoproteome of herpes simplex virus type 1. - Ieva Bagdonaite; Rickard Nordén; Hiren J Joshi; Sally Dabelsteen; Kristina Nyström; Sergey Y Vakhrushev; Sigvard Olofsson; Hans H Wandall (PLoS Pathogens, 2015)
Glycosylation of viral envelope proteins is important for infectivity and interaction with host immunity, however, our current knowledge of the functions of glycosylation is largely limited to N-glycosylation because it is difficult to predict and identify site-specific O-glycosylation. Here, we present a novel proteome-wide discovery strategy for O-glycosylation sites on viral envelope proteins using herpes simplex virus type 1 (HSV-1) as a model. We identified 74 O-linked glycosylation sites on 8 out of the 12 HSV-1 envelope proteins. Two of the identified glycosites found in glycoprotein B were previously implicated in virus attachment to immune cells. We show that HSV-1 infection distorts the secretory pathway and that infected cells accumulate glycoproteins with truncated O-glycans, nonetheless retaining the ability to elongate most of the surface glycans. With the use of precise gene editing, we further demonstrate that elongated O-glycans are essential for HSV-1 in human HaCaT keratinocytes, where HSV-1 produced markedly lower viral titers in HaCaT with abrogated O-glycans compared to the isogenic counterpart with normal O-glycans. The roles of O-linked glycosylation for viral entry, formation, secretion, and immune recognition are poorly understood, and the O-glycoproteomics strategy presented here now opens for unbiased discovery on all enveloped viruses.